Natural amenities and low-density residential development: Magnitude and spatial scale of influences. (March 2021) - Reisig, Dawson; Mullan, Katrina; Hansen, Andrew; Powell, Scott; Theobald, David; Ulrich, Rachel
Highlights: We use high resolution imagery to identify and model patterns of low-density residential development. We estimate relationships between natural amenities and low-density development at multiple scales. Plots near public lands and lakes with mixed vegetation are more likely to be developed. Communities near National Parks, other public lands and ski resorts experienced greater overall development pressures. Our results can inform conservation prioritization and planning, in the context of environment-development tradeoffs. Abstract: Low-density residential development in rural areas is an important land use trend in many parts of the world, and has disproportionate ecological impacts due to its large footprint relative to population. It is widely suggested that this type of land use change is driven in part by natural amenities, raising the concern that locations of high natural value are most rapid to develop. We examine the contribution of natural amenities to the probability of low-density development controlling for more traditional drivers of land use change. We do so considering the influence of natural amenities at two scales, individual plots, and the larger communities in the immediate vicinity. We use a unique primary dataset based on photo interpretation of high resolution imagery to capture residential development at the scale of a single house between 1990 and 2010. We combine these data with spatially-referenced census and other secondary data to estimate a multilevel regression model of the probability of residential land conversion. Our results demonstrate that communities near National Parks, other public lands and ski resorts experienced significantly higher rates of residential land conversion than those further from these amenities. Within communities, undeveloped plots that were 10 min closer than average to public land had a 67 % higher probability of conversion to residential use holding other characteristics constant, plots that were 75 min closer than average to a large lake had a 139 % higher probability of conversion, and plots with 1 standard deviation more forest/non-forest variation had a 44 % higher probability of conversion. Our findings regarding community and plot level influences of natural amenities on rural development are unique in the land use literature, and are important for identifying which communities and individual parcels have the highest probability of development. This can inform policy makers' and conservationists' efforts to protect places facing the highest threats, and help both regional and local land-use planners manage tradeoffs between environmental protection and economic growth.